2021
DOI: 10.1002/tox.23301
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic effects of Prunella vulgaris against fluoride‐induced oxidative damage by using the metabolomics method

Abstract: Fluoride is considered as one of the most ubiquitous environmental pollutants. Numerous studies have linked reactive oxygen species (ROS)‐dependent oxidative damage with fluoride intoxication, which could be prevented by antioxidants. However, the metabolomic changes induced by ROS disruptions in fluoride intoxication are yet unknown. The present study aimed to provide novel mechanistic insights into the fluoride‐induced oxidative damage and to investigate the potential protective effects of ethanolic extract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…As the most important metabolic organ, the liver plays a significant role in regulating glycolipid metabolism homeostasis in the body . Literatures have reported that fluoride could affect the biological processes of gluconeogenesis, glycolysis, and lipid peroxidation, resulting in decreased carbohydrates and increased lipids in the liver, which disrupts the homeostasis of glycolipid metabolism in the body. , These findings were confirmed in this study; fluoride caused the reduction of glycogen content and the increase of the number of lipid droplets and the content of TG, TC, HDL, and LDL in the liver, which suggested that fluoride resulted in the disturbances of hepatic glycolipid metabolism.…”
Section: Discussionsupporting
confidence: 86%
“…As the most important metabolic organ, the liver plays a significant role in regulating glycolipid metabolism homeostasis in the body . Literatures have reported that fluoride could affect the biological processes of gluconeogenesis, glycolysis, and lipid peroxidation, resulting in decreased carbohydrates and increased lipids in the liver, which disrupts the homeostasis of glycolipid metabolism in the body. , These findings were confirmed in this study; fluoride caused the reduction of glycogen content and the increase of the number of lipid droplets and the content of TG, TC, HDL, and LDL in the liver, which suggested that fluoride resulted in the disturbances of hepatic glycolipid metabolism.…”
Section: Discussionsupporting
confidence: 86%
“…Different polyphenols have been identified in P. vulgaris L., such as phenolic acids and flavonoids [7][8][9]. To date, antioxidant activity of P. vulgaris L. has been evaluated [10]. However, α-glucosidase inhibitory activity of P. vulgaris L. has not been explored.…”
Section: Analysis Of Total Phenolic Content α-Glucosidase Inhibitory ...mentioning
confidence: 99%
“…Prunella vulgaris L. has been widely used in traditional Chinese medicine for liver heat clearing, fire dispersing, eyesight improving, mass resolving, and swelling reduction [7]. Modern pharmacological studies reveal its antioxidant, anti-diabetes, antimicrobial, anti-tumor, anti-inflammatory, and anti-HIV effects [8][9][10]. And in Asian folk medicine, P. vulgaris L. has been used for blood glucose homeostasis and antioxidant potential [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations